Phylogenomics and structural variations of plastid genomes of the columbine genus (Ranunculaceae) - Fang-Min Yu; Wen-Chuang He; Andrey S. Erst; Huan-Wen Peng; Yuan-Yuan Ling; Tatyana V. Erst; Michael V. Bardukov; Wei Wang; Kun-Li Xiang (BMC Plant Biology)
Abstract Background The columbine genus (Aquilegia) contains many species with horticultural and pharmaceutical importance. However, a well-resolved phylogeny for this genus remains lacking owing to recent and rapid radiation. We obtained plastomes of 75 Aquilegia species and six species of other genera in Thalictroideae to reconstruct a robust phylogeny for Aquilegia. Within the phylogenetic framework, we investigated the evolutionary patterns of structural variations in Aquilegia plastomes. We also examined appropriate molecular markers for species identification of this genus. Results Plastid phylogenomic analyses show that Aquilegia is monophyletic and divided into two major clades and eight subclades, largely in agreement with species geographical distributions. Aquilegia plastomes have copy number variations (CNVs) of genes at the boundaries of IR/SC regions. An inversion was identified in the large single-copy region (LSC) plastomes of Aquilegia, Semiaquilegia, and Urophysa. The inversion was adjacent to three distinct structures (type I-III) in LSC region, each characterized by presence or absence of different short inverted repeat (sIR) regions. The most recent common ancestor of Aquilegia species was type III, and other two types were derived by shortening or loss of sIRs. Ten hypervariable regions were identified in Aquilegia plastomes. Conclusions We present a well-resolved phylogeny for Aquilegia. The CNVs of genes were observed frequently at the boundaries of IR/SC regions and sIR regions in the genus, and the inversions and sIR in LSC regions have phylogenetic signal and lead to notable variations in gene content and length of plastomes. The new hypervariable regions can be used for phylogenetic analyses and molecular identification of Aquilegia. This study provides new insights into the structural evolution of plastome in angiosperms, and also have important implications for the conservation and utilization of Aquilegia species.